2017
DOI: 10.1016/j.mib.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CRISPR-Cas systems by mobile genetic elements

Abstract: Clustered, regularly interspaced, short, palindromic repeats (CRISPR) loci, together with their CRISPR-associated (Cas) proteins, provide bacteria and archaea with adaptive immunity against invasion by bacteriophages, plasmids, and other mobile genetic elements. These host defenses impart selective pressure on phages and mobile elements to evolve countermeasures against CRISPR immunity. As a consequence of this pressure, phages and mobile elements have evolved “anti-CRISPR” proteins that function as direct inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…To counteract CRISPR-Cas immunity, phages employ inhibitory proteins to inactivate CRISPR-Cas function in a sequenceindependent manner (Bondy-Denomy et al, 2013;Sontheimer and Davidson, 2017). To date, >40 diverse anti-CRISPRs have been identified in phages, prophages, and mobile genetic elements (Borges et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To counteract CRISPR-Cas immunity, phages employ inhibitory proteins to inactivate CRISPR-Cas function in a sequenceindependent manner (Bondy-Denomy et al, 2013;Sontheimer and Davidson, 2017). To date, >40 diverse anti-CRISPRs have been identified in phages, prophages, and mobile genetic elements (Borges et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, just one of the 130 18 contigs from this library was found to be phage-associated (table S4) (table S3). Many contigs from these libraries are phage-associated (30%; table S4, 141 figure 2A) and many encode genes of unknown function (figure S4); these are both hallmarks of known 142 acrs (Borges et al, 2017;Pawluk et al, 2017;Sontheimer and Davidson, 2017). Additionally, we 143 observed that Cas9 homologs are found in 15 of the 18 bacterial genera identified in these selections 144 (83%, table S4), a significant enrichment over the 12% of bacterial genera that harbor Cas9 (567/4822) 145 from a representative set of ~24,000 bacterial genomes (Mendler et al, 2018) (p=4x10 -21 , χ² test).…”
Section: Introduction 14mentioning
confidence: 99%
“…These clever strategies have revealed many 49 candidate acrs. But they have also highlighted the difficulty of finding new acr genes based on homology, 50 since acrs share little sequence conservation (Sontheimer and Davidson, 2017). As a result, most acrs 51 almost certainly lie unrecognized among the many genes of unknown function in phages, plasmids, and 52 other MGEs (Hatfull, 2015).…”
mentioning
confidence: 99%
“…In this pipeline, new acr gene candidates are identified by their proximity to predicted helix-turn-helix (HTH) transcriptional regulator genes known as anti-CRISPR associated ( aca ) genes 16 . We identified ORFs encoding uncharacterized small [~50-150 amino acids (aa)] proteins immediately upstream of aca homologues, focusing on genomic regions near putative phage- or MGE- associated sequences 3, 4, 24 . These criteria led us to focus on two putative Acr candidates: an 88 aa hypothetical protein in the genome of H. parainfluenzae strain 146_HPAR (NCBI RefSeq accession WP_049372635) and a 120aa hypothetical protein in the genome of S. muelleri strain ATCC 29453 (WP_002642161.1; Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%